PROFITABILITY, COMPANY SIZE, AND PROFIT PERSISTENCE INFLUENCE EARNING RESPONSE COEFFICIENT - Fatmawati, Mira; Nugroho, Danang; Novesar, Muhammad Refki; Nurhayati, Tita; Rizkiyah, Tiara Fitri; Pratama, Angga (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The purpose of this study is to find out how Profitability, Firm Size, and Profit Persistence affect theEarnings Response Coefficient. In this research, the sample is made up of companies in the consumergoods sector that were listed on the Indonesia Stock Exchange from 2017 to 2021. The sample is madeup of 16 companies that meet the sample criteria, which were set using a method called